Early weaning in pregnant cows as a fetal programming strategy alters the muscle metabotype and carcass traits in Nelore cattle - Matheus Sousa de Paula Carlis; Gabriela Abitante; Thiago Kan Nishimura; Carl Robertson Dahlen; Nara Regina Brandão Cônsolo; Luiz Alberto Colnago; Fernanda Maria Marins Ocampos; Germán Darío Ramírez-Zamudio; Patricia Maloso Ramos; Saulo Luz Silva; Miguel Henrique de Almeida Santana; Arlindo Saran Netto; et al. (Tropical Animal Health and Production, 2026)
This study evaluated early weaning (EW) versus conventional weaning (CW) and dam parity (DP) effects on carcass traits, meat quality, and the muscle metabolome of male offspring exposed in utero during the intervention. A randomized complete-block design with a 2 × 2 factorial arrangement compared weaning strategies (WS: EW at 150 d lactation/80 d gestation vs. CW at 240 d lactation/170 d gestation) and dam parities (DP: multiparous [MP] vs. secundiparous [SP]). Carcass and meat quality data were analyzed considering the dams as experimental unit by using the Mixed procedure, considering the WS and DP as fixed effect, and their interaction. There was interaction between WS×DP ( P < 0.01) for hindquarter fat trim where EW-MP and CW-MP carcasses required more trim fat than EW-SP. EW bulls tended to reduce drip loss ( P = 0.07), tended to increased pistola hindquarter (% of carcass; P = 0.09), while significantly raising ultimate carcass pH ( P = 0.04) versus CW. An untarget 1 H NMR-based metabolomic approach was applied to detect metabolic changes. Pathway analysis of differentially abundant metabolites revealed the upregulation of betaine and glycerolipid metabolism, methylhistidine metabolism for WS and homocysteine degradation, phosphatidylethanolamine synthesis and selenoamino acid metabolism for DP. Offspring of MP dams had heavier cold carcasses ( P = 0.03), greater Forequarter, brisket, shank ( P < 0.03), smaller pistola hindquarter and top sirloin cap ( P ≤ 0.05) than those of SP. These results indicate that WS and DP induce metabolomic shifts favoring muscular hypertrophy and one-carbon metabolism, which may enhance muscularity without impairing meat quality.